1997
DOI: 10.1021/ma9614510
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion Polymerization of Styrene Using Conventional, Polymerizable, and Polymeric Surfactants. A Comparative Study

Abstract: The emulsion polymerization of styrene is investigated, employing analogous conventional, polymerizable, and polymeric cationic surfactants (“polysoaps”). The polymerization and the properties of the latexes depend sensitively on the emulsifier and on the charge of the initiator. There is no visible correlation between the properties of the final latexes and the properties of the emulsifiers such as surface activity, solubilization capacity, or the ability to stabilize the initial monomer emulsion. When a cati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 47 publications
2
77
0
1
Order By: Relevance
“…Cochin et al [60] carried out a comparative study using polymerizable and non-polymerizable cationic surfactants in the emulsion polymerization of styrene. It was found that when a cationic initiator was used, the latexes prepared with the polymerizable analogue presented better freeze-thaw stability.…”
Section: Reported Product Improvementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cochin et al [60] carried out a comparative study using polymerizable and non-polymerizable cationic surfactants in the emulsion polymerization of styrene. It was found that when a cationic initiator was used, the latexes prepared with the polymerizable analogue presented better freeze-thaw stability.…”
Section: Reported Product Improvementsmentioning
confidence: 99%
“…Cochin et al [60] found that the batch emulsion polymerization of styrene using a cationic emulsifier proceeded smoothly leading to stable latexes at a relative high polymerization rate when a cationic initiator was used. However, coagulation occurred when anionic potassium persulfate was employed.…”
Section: Polymerization Locimentioning
confidence: 99%
“…Potassium persulfate (PPS, Sigma) was chosen as initiator, acrylamide (BASF) as hydrophilic monomer, and nonylphenol (NP20, where 20 designates the average length chain of the ethoxylate, the molar mass of which is 1084 g/mol) as a surfactant. The hydrophobic monomers (EHA and the IBA) were selected because they have boiling points higher than polymerization temperature and they have a certain degree of solubility in water, which is good for the emulsion polymerization [12].…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] Previous investigations have developed block or graft amphiphatic polymeric emulsifiers, polyelectrolytes, and polysoap emulsifiers. [5][6][7][8][9][10] Among the various polymeric emulsifiers, polyester-based emulsifiers are of paramount concern. 3,4,[11][12][13] Almost all previous studies of polymeric emulsifiers have focused on the structural design of the molecules.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In addition, micellar nucleation is involved in polymerizations with polymeric emulsifiers. 6,9 In conventional emulsion polymerization for a low-water-soluble monomer, the monomer is emulsified into the continuous aqueous phase, monomer droplets 1-10 m in size are formed, and most of the emulsifiers are either dissolved in the continuous phase or are in the form of micelles. The large total surface area of the micelles compared with the area of the monomer droplets greatly favors the micelles in the initial absorption of aqueous-phase-formed free radicals.…”
Section: Introductionmentioning
confidence: 99%